Pre‐amyloid stage of Alzheimer's disease in cognitively normal individuals. Issue 9 (20th July 2018) - Tijms, Betty M.; Vermunt, Lisa; Zwan, Marissa D.; van Harten, Argonde C.; van der Flier, Wiesje M.; Teunissen, Charlotte E.; Scheltens, Philip; Visser, Pieter Jelle; ,
Abstract: Objective: To study risk factors for decreasing a β 1–42 concentrations in cerebrospinal fluid (CSF) in cognitively unimpaired individuals with initially normal amyloid and tau markers, and to investigate whether such a β 1–42 decreases are associated with subsequent decline in cognition and other biomarkers of Alzheimer's disease. Methods: Cognitively normal subjects ( n = 83, 75 ± 5 years, 35(42%) female) with normal CSF a β 1–42 and tau and repeated CSF sampling were selected from ADNI. Subject level slopes of a β 1–42 decreases were estimated with mixed models. We tested associations of baseline APP processing markers (BACE1 activity, a β 1–40, a β 1–38 and sAPP β ) and decreasing a β 1–42 levels by including an interaction term between time and APP marker. Associations between decreasing a β 1–42 levels and clinical decline (i.e., progression to mild cognitive impairment or dementia, MMSE, memory functioning) and biological decline (tau, hippocampal volume, glucose processing and amyloid PET) over a time period of 8–10 years were assessed. Results: A β 1–42 levels decreased annually with −4.6 ± 1 pg/mL. Higher baseline BACE1 activity ( β (se) = −0.06(0.03), P < 0.05), a β 1–40 ( β (se)= −0.11(.03), P < 0.001), and a β 1–38 levels ( β (se) = −0.11(0.03), P < 0.001) predicted faster decreasing a β 1–42 . The fastest tertile of decreasing a β 1–42 rates was associated with subsequent pathophysiological processes: 11(14%) subjects developed abnormal amyloid levels after 3 ± 1.7 years, showed increased risk for clinical progression (Hazard Ratio[95CI] = 4.8[1.1–21.0]), decreases in MMSE, glucose metabolism and hippocampal volume, and increased CSF tau and amyloid aggregation on PET (all P < 0.05). Interpretation: Higher APP processing and fast decreasing a β 1–42 could be among the earliest, pre‐amyloid, pathological changes in Alzheimer's disease.